Healthy Environment Development in School Health Units of Public Primary Schools in Bontobahari Bulukumba - Hasriana Sari; Nuurhidayat Jafar; Silvia Malasari (Universitas Hasanuddin, 2018)
Background: School Health Unit is an effort to build healthy habits in order to improve students health through three main programs, namely health education, health services, and healthy environment development. Development of school resilience was conducted through a healthy school environment. Due to improving the health of school communities, an healthy school environment should be created. Purpose: To identify the indicators of healthy school environment development of school health unit program: at Public Primary Schools in Bontobahari Bulukumba district. Methods: The descriptive survey with cross sectional study design. The population of 27 schools with random cluster sampling technique. The obtained samples were 13 schools. Results: The results showed that there were 10 schools (76.9%) with good category and three schools (23.1%) with adequate category. All the schools meet the indicator of the room and buldings, lighting, garbage, noise, and sewerage. Most of the schools meet the indicator of the board distance, classroom density, clean water, cafeteria/eatery, and school grounds. Only a limited number of schools meet the indicator of the ventilation, hand-washing facility, and behavior. All the schools eligible indicators of the learners table and WC/Toilet. Conclusion: The development of healthy school environment at Public Primary Schools on sub-district of Bontobahari in Bulukumba district were in good category. It is hoped that the next researcher would examine other indicators overview of school health unit program, namely health education and health service.